Metode Pelaksanaan Perbaikan Tanah Menggunakan Metode Preloading dan Prefabricated Vertical Drain (PVD) Pada Pembangunan Jalan Lingkar Utara Lamongan - Denis Tiyas Ayu Saputri; Fiarestu Wahyu Dewanti; Raihan Bryne Firdaus Al Machrus; Syahrizal Abdullah Razak; Dika Ayu Safitri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The construction implementation method is a very important part of the construction project to obtain the objectives of the project, the cost, quality and time. The technology aspect is very important in a construction project. Using the method of proper, practical, fast, and safe is very helpful in a construction project. Preloading and Prefabricated Vertical Drain (PVD) methods are intended to accelerate settlement and increase the bearing capacity of soft native soils by reducing pore water through PVD in the soil with the intention of reducing water content or air content in soil grains so as to accelerate long-term settlement. Preloading with PVD can reduce the material used for pre-loading, reduce embankment material, accelerate consolidation time, and increase embankment stability.